Quality Difference Analysis of Summer and Autumn White Tea from 5 Kinds of Tea Plant Varieties in Hanzhong Tea Area - Chenxi YANG; Jing FU; Jia LIU; Xinrui ZHAO; Xiaomeng SHEN (Shipin gongye ke-ji)
To explore the quality differences of summer and autumn white tea from different tea plant varieties, Shoumei white tea samples were manufactured of fresh leaves in summer and autumn from 5 kinds of tea plant varieties (Fuding Dabai, Shancha 1, Pingyang Tezao, Beiba group, Cuifeng) in Hanzhong tea area. White tea samples were analyzed the quality with the method of sensory evaluation, and main physicochemical properties and volatile components were determined by the method of high performance liquid chromatography (HPLC), gas chromatography-ion mobility spectrometry (GC-IMS) and other detection methods. Results showed that Cuifeng summer and autumn white tea had the highest sensory review scores among all samples in the same season, with 91.6 and 89.8 points respectively. Water extract, tea polyphenol, total free amino acids, phenol-ammonia ratio, caffeine, total catechins were 46.78%~50.50%, 16.71%~22.59%, 4.41%~5.46%, 3.43~2.15, 3.39%~5.36%, 14.91%~21.42% in summer, and 42.30%~49.62%, 17.60%~24.32%, 2.94%~3.33%, 5.69~8.18, 3.40%~4.49%, 13.29%~20.34% in autumn, respectively. Contents of total free amino acid (5.46%) and caffeine (5.36%) of white tea from Cuifeng in summer were highest. A total of 102 kinds of volatile components were detected, and 82 volatile components were qualitatively identified, including 28 aldehydes, 19 alcohols, 14 ketones, 7 acids, 6 furans, 5 esters, 2 pyrazines and 1 cyclic oxide. Relative content of aldehydes was the most (33.70%~36.86%), followed by alcohols (24.80%~26.78%). 1-Propanol, 2-methyl-1-propanol and 2-methyl-1-butanol of white tea from Cuifeng in summer were highest. Volatile components of white tea from different tea plant varieties and seasons were effectively distinguished by principal component analysis (PCA) method. In conclusion, there are significant differences among main physicochemical properties and volatile components of samples in summer and autumn. The suitability of white tea from Cuifeng in summer is the best in Hanzhong tea area. This study is expected to provide data support for white tea production and challenging chance for high-value utilization of fresh tea leaves in summer and autumn in Hanzhong tea area.